CYBERSECURITY CHALLENGES IN THE AGE OF DIGITAL TRANSFORMATION - Qilichova Matluba Kamolovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: Digital transformation has become a strategic priority for organizations across all sectors, enabling improved efficiency, innovation, and competitiveness. However, the rapid adoption of digital technologies such as cloud computing, artificial intelligence (AI), Internet of Things (IoT), and big data has significantly expanded the cyber threat landscape. This paper examines the major cybersecurity challenges emerging in the age of digital transformation, including increased attack surfaces, data privacy risks, skill shortages, and regulatory complexities. The study also discusses potential strategies and best practices to enhance cybersecurity resilience in digitally transformed environments.